Pengaruh Kepemimpinan Transformasional Kepala Sekolah dan Budaya Sekolah Terhadap Kinerja Guru pada Sekolah Pengerak SMA di Kecamatan Sirimau Kota Ambon - Rumakabes, Hasanudin; Kempa, R.; Rumfot, Sumarni (LP. Ma'arif Janggan Magetan, 2024)
Supervision needs to be prepared by the school principal and socialized to teachers through school meetings, so that teachers know and understand the aims and objectives of the supervision program. Supervision is seen from the planning, implementation and evaluation of supervision itself as a system, and leads to two elements of supervision, including (1) academic supervision and (2) managerial supervision. This research was carried out at SMP Negeri 11 East Seram, SMP Negeri 33 East Seram, and SMP Negeri 41 Seram Timur. This research aims to describe planning, implementation, evaluation and supporting and inhibiting factors for head supervision management. Qualitative data analysis methods are used to answer research results from interviews and observations. Data was analyzed through data reduction, data display and drawing conclusions. The results of this research show that school principals plan academic supervision programs by involving teachers in determining the supervision schedule. This supervision activity includes planning and assessing the learning process, planning, while implementation activities include assessing the progress of the learning process which involves the use of learning strategies/methods/techniques and classroom management, the implementation of academic and managerial supervision carried out by assigned supervisors. Academic supervision evaluations are carried out by the principal in various ways, evaluations are delivered simultaneously or to many teachers, evaluations are carried out in groups or meetings are held at the end of the month or end of the semester. Supporting factors for implementing academic supervision are availability of time, socializing the schedule and providing motivation to teachers. Meanwhile, the inhibiting factor is insufficient time allocation in carrying out academic supervision. conclusions in this research from the planning aspect. The principal makes a plan before supervising the teacher. From the implementation aspect, the principal carries out the supervision program in accordance with what has been programmed at a predetermined time. From the evaluation aspect, the supervision carried out by the principal aims to correct everything that is lacking from the teacher. in schools, evaluations are carried out in groups or meetings are held at the end of the month or end of the semester, if the evaluation is only a few teachers then the evaluation is carried out individually. In conclusion, the principal first does the planning, provides space and opportunities to develop his/her teaching competence